Analisis Perkembangan Keterampilan Motorik Siswa Kelas V SD Namira Kraksaan dengan Fokus Kemampuan Profisiensi Tubuh (Physical Proficiency Ability) - Muhammad Alfan Rizqi (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2022)
Students in elementary school really need the right motor skill development process in order to get an optimal level of development. Development can be done properly if the teacher already knows the level of students' basic motor skills. The purpose of this study was to improve children's motor skills with a focus on body proficient abilities in fifth grade students of SD Namira Kraksaan. This research is a qualitative research with a descriptive approach to 20 students. The study used three test items to determine the motoric development of students, including sitting up, long jump, and sit-ups. The results of the first session of the study showed that there was 1 student who did not pass the sit-up test. The treatment given is focused on the sit-up test, which is doing the sit-up steps correctly. The conclusion of this study is that the application of sit-up learning activities can support the completeness of students' motor development test results.